Sn-doped/coated Ni-Rich LiNi0.90Co0.04Mn0.03Al0.03O2 cathode materials for improved electrochemical performance of li-ion batteries - Jeyakumar, Juliya; Seenivasan, Manojkumar; Wu, Yi–Shiuan; Kuo, Liang-Yin; Wu, She–Huang; Chang, Jeng-Kuei; Rajan, Jose; Yang, Chun-Chen (American Chemical Society, 2024)
Ultrahigh nickel-rich cathode materials possess high gravimetric capacity but are restricted by poor structural stability and aggressive deterioration on long cycling. In this study, a doping-coating strategy for the Ni-rich LiNi0.90Co0.04Mn0.03Al0.03O2 (denoted as NCMA) cathode is proposed, with the addition of various mol % Sn to achieve Sn doping (SnO2 was used as a dopant to replace Ni) and coating. The physical and electrochemical properties of the modified cathode material were studied using scanning electron microscopy (SEM), X-ray diffraction (XRD), in situ XRD analysis, X-ray photoelectron spectroscopy (XPS), and Galvanostatic charge–discharge (GCD). The substitution of Sn4+ ions had no adverse impact on the crystal structure while alleviating the strain on the c-axis contraction, as confirmed by in situ XRD analysis. The strong Sn–O bond reinforced the structural integrity, while the inert coating layer helped build robust interfacial stability on prolonged cycling compared to that of an unmodified cathode. Doping with an appropriate amount of Sn4+ resulted in a marked improvement in the electrochemical performance of the LiNi0.90–xCo0.04Mn0.03Al0.03SnxO2 (where x = 0, 0.003, 0.006, and 0.012) cathode material. The optimal performance was achieved when x = 0.006; the Sn-modified LiNi0.90Co0.04Mn0.03Al0.03O2 cathode exhibited a discharge capacity of 203.5 mAh g–1 and capacity retention of ∼93% after 100 cycles and ∼83% after 200 cycles at 4.3 V, along with ∼88% retention at 4.5 V after 100 cycles at 1 C. The performance difference was more pronounced at higher rates, with the Sn-0.6 sample exhibiting an improved discharge capacity of 142.3 mAh g–1 at 10 C, compared to that of the bare LiNi0.90Co0.04Mn0.03Al0.03O2 (100.6 mAh g–1). Our proposed simultaneous doping-coating strategy using Sn for LiNi0.90Co0.04Mn0.03Al0.03O2 presents a viable approach for enhancing the performance of Ni-rich cathode materials.